Influence of saturation level on the acoustic emission characteristics of gas hydrate-bearing coal - Kang Yu; Yu Miao; Zhu Jinchao (Scientific Reports, 2024)
Abstract To study the effects of gas hydrates on the prevention and control of coal and gas protrusions, this paper reports the results of acoustic emission experiments on coal bodies containing gas hydrates with different saturation levels. The results showed that few acoustic emission events were generated in the elasticity stages of coal bodies containing gas hydrates, and the first sudden increase in the number of ringing counts generally occurred before and after the yielding point. Additionally, the acoustic emission events in the yielding stage were more active, and the cumulative number of ringing counts increased faster. The peak ringing counts appeared around the damage point, and a small number of acoustic emission events were still generated after destruction of the coal samples. The cumulative ringing counts decreased linearly with increasing saturation. The effect of saturation on the cumulative ringing counts in the elasticity stage of the gas hydrate-containing coal samples was small, but the difference between the cumulative ringing counts in the yielding stage and those in the destruction stage was larger. The total cumulative ringing counts and the cumulative ringing counts during each stage for the gas hydrate-containing coal samples decreased with increasing enclosure pressure. The energy and amplitude of the loading process were consistent with the trend for the ringing counts. The acoustic emission ringing counts of gas-containing coals were greater than those of gas hydrate-containing coals in the yielding and destructing stages.